Phytodiversite Et Pharmacopée Traditionnelle De La Communauté Kaamba De Madingou (Bouenza - Congo) - Kimpouni, Victor; Lenga-Sacadura, Marie-Yvette; Mamboueni, Josérald Chaîph; Mikoko, Elie Nsika (European Scientific Journal, ESJ, 2018)
The ethnobotanical study carried out at Madingou (4°16’ S, 13°33’ E) focuses on medicinal plants of the savannah zone. The survey used personal interviews and focus groups. Informants consisted of the inhabitants, whose age varies from 18 to 60 years or more. A total of 80 plant species were cited in the traditional pharmacopoeia. These plants are used in 66 recipes for treating 43 different diseases and symptoms, grouped in 11 major affiliations following the disease and symptoms sphere. Infectious and parasitic diseases is the most important group (23.25%), followed by the ill-defined symptoms and signs (13.95%) and the digestive system (11.63%). Five modes of administration were noted. The most preferred being the oral voice (38.75%). Among the 7 types of plant parts cited, leaves (65%) are preponderant. 8 modes of preparation were cited, the decoction (23.75%) being the most common. Of the 80 species listed, Allium sativum, Persea americana, Solanum nigrum, are among the medicinal plants most commonly used in Africa. Of the remaining species, 9 have been the subject of phytochemical studies all over the world. Ethnobotanical data show that a number of taxa, the medicinal properties of which are proved elsewhere, exist in the region and are not exploited, such as Millettia laurentii. Several species inventoried cover more than one aspect of indigenous knowledge, they are referred to as multipurpose plants and therefore the most vulnerable of the anthropic influences.